2019
DOI: 10.1142/s2339547819500043
|View full text |Cite
|
Sign up to set email alerts
|

Repopulation of intrahepatic bile ducts in engineered rat liver grafts

Abstract: Engineered liver grafts for transplantation with sufficient hepatic function have been developed both in small and large animal models using the whole liver engineering approach. However, repopulation of the bile ducts in the whole liver scaffolds has not been addressed yet. In this study, we show the feasibility of repopulating the bile ducts in decellularized rat livers. Biliary epithelial cells were introduced into the bile ducts of the decellularized liver scaffolds with or without hepatocytes in the paren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 37 publications
(44 reference statements)
0
11
0
Order By: Relevance
“…Another approach is hepatocyte transplantation, which is restricted by the low liver-engraftment rate and low survival rate of the transplanted hepatocytes (Ibars et al, 2016 with healthy liver cells such as primary or stem-cell-derived hepatocytes and nonparenchymal cells, especially with endothelial cells (Acun et al, 2019;Wang et al, 2017). The repopulation of the IHBDs, which is a critical component of the nonparenchymal population, has not been addressed in the engineered liver grafts until recently (Chen et al, 2019). The integration of BC to the bile ducts within engineered liver tissues is yet to be shown.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another approach is hepatocyte transplantation, which is restricted by the low liver-engraftment rate and low survival rate of the transplanted hepatocytes (Ibars et al, 2016 with healthy liver cells such as primary or stem-cell-derived hepatocytes and nonparenchymal cells, especially with endothelial cells (Acun et al, 2019;Wang et al, 2017). The repopulation of the IHBDs, which is a critical component of the nonparenchymal population, has not been addressed in the engineered liver grafts until recently (Chen et al, 2019). The integration of BC to the bile ducts within engineered liver tissues is yet to be shown.…”
Section: Discussionmentioning
confidence: 99%
“…The repopulation of the intrahepatic bile ducts (IHBDs), which is a critical component of the nonparenchymal population, has been largely neglected in the engineered liver grafts until recently (Chen, Devalliere, Bulutoglu, Yarmush, & Uygun, 2019). IHBD constitute the biliary network formed by the cholangiocytes, or bile duct epithelial cells, whose primary role is to modify and transport the bile formed by the hepatocytes.…”
Section: Introductionmentioning
confidence: 99%
“…In the last 10 years, a variety of animal models, decellularisation techniques, repopulation routes and cell sources have been described, with promising outcomes in terms of vascular repopulation[ 118 , 129 , 130 ], hepatocyte survival[ 131 ] as well as formation of biliary duct-like structures and activation of liver detoxification enzymes[ 132 ]. One of the commonest sources of liver scaffolds is the rat[ 118 , 127 , 132 - 137 ] repopulated with rat hepatocytes (although cholangiocytes[ 136 ] and lineages from pluripotent stem cells, mesenchymal cells, and fibroblasts have also been described[ 137 ] usually via the portal vein. With regards to human tissue, Verstegen et al [ 138 ] demonstrated that decellularised human livers can be repopulated with human umbilical vein endothelial cells, leading to re-endothelialisation of the vascular tree.…”
Section: Section 1: Models Of Liver Regenerationmentioning
confidence: 99%
“…The use of bile duct cells was demonstrated using rat liver scaffolds first repopulated with cholangiocytes through the extrahepatic biliary tree and then with hepatocytes via portal vein perfusion. 36 3D bioprinting can also be used to recreate the spatial relationship between different cell types, thus mimicking the native tissue microarchitecture. In this technology, a 3D printer layers biomatrix, such as hydrogel, and cells upon each other to create the desired structure.…”
Section: Biliary Organoids and Regenerative Medicinementioning
confidence: 99%